PEMBERDAYAAN PEREMPUAN OLEH ORGANISASI AKAR RUMPUT (KASUS PERAN KOPERASI KELOMPOK PENGAJIAN DI DESA SRIWULAN KABUPATEN DEMAK) - Untari, Sri (Forum Ilmu Sosial, 2009)
This study shows that the empowerment of local women through the organization formed by their own efforts more effective than others who come from outside their community. The village is a village Sriwulan transition from traditional culture to modern culture. These changes are marked by the emergence of local institutions, namely the organization of grass-roots organizations (grassroots organizations) are diverse and have an important role in community empowerment. Local institutions appear on the initiative of the community and have a real agenda to strengthen the public welfare efforts. An important found role in this research is a study group of mothers who do women’s empowerment activities of its members, not just on matters of religion, but also social issues, economics, and art.Keywords: Empowerment of women, the organization of grass-roots